An Exploration of Bioremediation and Its Implementation in Processing of Aquaculture Waste (International Journal of Innovative Research in Engineering & Management, 2021)
Environmental implications of waste generated by large-scale,  intensive aquaculture are substantial, and they have the potential  to cause dynamic habitat changes. Inorganic nitrogen will be  captured from water by using both current and new technology,  and organic nitrogen will be reduced in sediments by using both  existing and creative technology. Environmental methods like as  Integrated Multi-Trophic Aquaculture (IMTA) are growing in  favor because to their ability to increase in situ nitrogen and  other nutrient reduction at sea cage locations. There has been  many research published on biological nitrogen removal via  nitrification, denitrification, and anaerobic ammonium  oxidation. This process includes a variety of bacterial species,  which has resulted in a lot of studies being published. More  efforts, however, must be undertaken to remediate wastewater  and aquatic sediments generated by water farming operations.  There are several drawbacks to traditional healthcare techniques,  which are listed below. The development of more efficient  reactor systems, as well as a complete, integrated waste  management solution, will promote the adoption of more  environmentally friendly aquaculture practices. This article  discusses the use of bioremediation for the treatment of  aquaculture effluent, and how it may be used.
Keywords: Aquaculture; Bioremediation; Denitrification; Microorganisms; Nitrification